IMPLEMENTASI NEW PUBLIC MANAGEMENT (NPM) TERHADAP REFORMASI BIROKRASI - Azijah, Siti Nur; Wahyudin, Cecep (Administratie: Jurnal Administrasi Publik, 2021)
Bureaucratic reform is something that needs to be done, especially in the public service sector, the development and transition of the era to an all-digital era has more or less an effect on the governance of the public service bureaucracy, such as the New Public Management (NPM) paradigm which is present to adjust the community's needs regarding renewable public services. This article describes the implementation of New Public Management (NPM) at the GRHA Tiyasa Public Service Mall, Bogor City. By using qualitative methods and literature study techniques to collect the necessary data and information and to find out more about the implementation of the New Public Management (NPM) implemented at the GRHA Tiyasa Public Service Mall, Bogor City.